Triindoles as excellent platforms for organic semiconductors: from crystalline molecules to porous polymers - Gámez-Valenzuela, Sergio; Ponce-Ortiz, Rocío; Ruiz-Delgado, María del Carmen (My University, 2022)
Organic semiconductors are one of the most promising candidates for next-generation electronics applications. In this sense, triindole-based systems have demonstrated great potential as p-type semiconductors in organic field-effect transistors (OFETs).1 In this project, a mixed experimental and theoretical study of three new crystalline N-trimethyltriindoles endowed with different functionalities at 3, 8 and 13 positions are investigated (Figure 1a), with the main goal of exploring the correlation between the electronic nature of the substituents and their solid-state organization and semiconductor behavior.2 On the other hand, the design and synthesis of covalent organic framework materials (constructed from the union of different covalently linked conjugated platforms) is being deeply investigated in organic electronic.3 Recently, in collaboration with the groups of Dr. Berta Gómez-Lor and Dr. Jose Ignacio Martínez, we have theoretically studied how the structural and the electronic properties of new porous triindole-based polymers (Figure 1b) can be modulated by the (i) modification of the linkage position from para (T2) to meta (T3), (ii) by the insertion of different π-bridges (phenylene or alkyne) between the cores and (iii) by the increment of the number of π-bridges from 3 to 6 units (T2,3).4
Keywords: Electrónica orgánica; Porosidad; Química física; Polímeros conductores; Conductores orgánicos; Dft calculations; Organic electronics; Charge transport; Porous polymers